The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3390/s17030502
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Unmanned Aerial Vehicle-Borne Crop-Growth Monitoring System

Abstract: In view of the demand for a low-cost, high-throughput method for the continuous acquisition of crop growth information, this study describes a crop-growth monitoring system which uses an unmanned aerial vehicle (UAV) as an operating platform. The system is capable of real-time online acquisition of various major indexes, e.g., the normalized difference vegetation index (NDVI) of the crop canopy, ratio vegetation index (RVI), leaf nitrogen accumulation (LNA), leaf area index (LAI), and leaf dry weight (LDW). By… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 29 publications
(27 reference statements)
1
25
0
Order By: Relevance
“…The results presented here not only confirm that these traits can be used to analyse crop responses to changes in treatment, but also prove that these indicators can be reliably obtained either by MGP or UAV imaging. Analysis of the crop growth as a function of interactions with soil and environmental conditions can subsequently provide customized management plans for farmers to maximize yield [48].…”
Section: Discussionmentioning
confidence: 99%
“…The results presented here not only confirm that these traits can be used to analyse crop responses to changes in treatment, but also prove that these indicators can be reliably obtained either by MGP or UAV imaging. Analysis of the crop growth as a function of interactions with soil and environmental conditions can subsequently provide customized management plans for farmers to maximize yield [48].…”
Section: Discussionmentioning
confidence: 99%
“…Mean height [3,9,12,13,15,16,[19][20][21]23,25,28,30,34,[48][49][50]57,58,63,65,[67][68][69][74][75][76] Maximum height [1,3,4,13,28,30,34,48,57,63,65,69] Minimum height [3,28,34,48,57,63,65,69] Median height [12,21,27,48,63,65,…”
Section: Heightmentioning
confidence: 99%
“…Previous research has revealed significant differences in the results of UAV RS-based crop growth monitoring due to the use of different sensors [14]. With the exception of a few studies using Lidar [52] and non-imaging active or passive canopy sensors [7,53], most of the UAV-based studies have used imaging spectrometers or multispectral [16,48] and hyperspectral cameras [19]. However, professional imaging sensors, UAV systems, and their supporting software may lead to a high total cost for ordinary consumers and cause challenges for technical promotion.…”
Section: Potential Of Consumer-grade Uav-based Digital Imagery For Crmentioning
confidence: 99%